2007
DOI: 10.1530/rep.1.01019
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity associated rise in leptin impairs ovarian activity during winter dormancy in Vespertilionid bat, Scotophilus heathi

Abstract: The aim of the study was to evaluate the seasonal variation in serum leptin levels in a natural population of the female bat, Scotophilus heathi and their relationship to the changes in the body mass, serum insulin level, and ovarian activity. Circulating leptin level varied significantly over the season and correlated positively with the changes in body mass, and circulating insulin and androstenedione (A4) levels. Circulating leptin concentrations showed two peaks; one coincides with the maximum fat accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 72 publications
6
35
0
Order By: Relevance
“…Although glycogen has an important role in energy homeostasis, several bat species rely mainly on lipid reserves to support reproductive activities (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008). The data obtained here seem to indicate that lipid reserves of male M. molossus remained unaltered in all seasons, except for the adiposity index.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although glycogen has an important role in energy homeostasis, several bat species rely mainly on lipid reserves to support reproductive activities (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008). The data obtained here seem to indicate that lipid reserves of male M. molossus remained unaltered in all seasons, except for the adiposity index.…”
Section: Discussionmentioning
confidence: 51%
“…It has been reported that insect-eating bats are able of fly while foraging powered by exogenous (dietary nutrients) rather than endogenous sources (glycogen or lipids) (Voigt et al, 2010). Reproductive activity in insect-eating bats also seems to require great energy expenditure, but this is based mainly on body lipid reserves stored during the previous seasons (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008).…”
Section: Discussionmentioning
confidence: 99%
“…Their ovaries were quickly taken out and cleaned of any adhered fat tissue and oviduct in DMEM (Himedia, Mumbai, India) containing 250 U/ml penicillin and 250 mg/ml streptomycin sulfate. Ovaries were cultured by the method as described previously (Srivastava & Krishna 2007) with some modifications. Culture medium was a mixture of DMEM (with sodium pyruvate and L-glutamine) and Ham's F-12 (1:1; v/v) Himedia) containing 100 U/ml penicillin, 100 mg/ml streptomycin, and 0.1% BSA (Sigma).…”
Section: Effect Of Melatonin On Ovarian Steroidogenesismentioning
confidence: 99%
“…Furthermore, protein extractions and immunoblotting were performed as described previously (Srivastava & Krishna 2007). Equal amount of proteins (50 mg) as determined by Folin's method was loaded on to SDS-PAGE (10%) for electrophoresis.…”
Section: Immunoblotmentioning
confidence: 99%
“…For example, in the Scotophilus heathii bat has been reported that serum leptin levels are positively correlated with body fat and negatively related to reproductive function [16][17].…”
Section: Introductionmentioning
confidence: 99%